(untitled) (Bulletin of criminological association of Ukraine, 2025)
The article analyzes the issue of translation and usage of the term «approximation" within the process of harmonizing Ukraine’s national legislation with the acquis of the European Union. It has been established that the lack of a unified approach to translating the term approximation leads to its varied interpretation in official documents, creating legal uncertainty and potentially affecting the effectiveness of the implementation of European legal norms in Ukraine. The key terminological discrepancies in the translations of acquis EU acts are outlined. The study examines the legal and linguistic aspects of the impact of translation inaccuracies on the law enforcement process. It has been found that terminological inconsistencies in the translations of international agreements, particularly the Association Agreement between Ukraine and the EU, may complicate the interpretation of the parties’ obligations and create difficulties in the process of legislative adaptation. It has been determined that the issue of translating legal terms is systemic in nature and requires the development of a unified approach to the use of legal terminology. Conceptual approaches to terminological standardization are proposed, which involve the use of a single equivalent for key terms and the alignment of translations with European standards.